TINGKAT PERTUMBUHAN, STRUKTUR AKTIVA, DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN PADA SEKTOR PERTAMBANGAN - Juliyanti, Ni Putu Indah; Sari, Maria Mediatrix Ratna (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023DO - 10.24843/EEB.2023.v12.i06.p04, 2023)
This study aims to determine the effect of growth rate, asset structure, and company size on company performance in the mining sector on the IDX for the 2018-2020 period. The population of this study are mining companies listed on the Indonesia Stock Exchange for the 2018-2020 period, totaling 41 companies. The sampling technique used was purposive sampling, so that the number of companies selected as samples was 35 companies, so that 105 observations were obtained during the research period. The analysis technique used in this research is multiple linear regression. The results of the study concluded that the growth rate had a significant positive effect on firm performance, asset structure had no significant effect on firm performance, while firm size had a significant negative effect on firm performance.